Flow and heat transfer of a power-law fluid over a permeable shrinking sheet - Nor Azizah Yacob; Anuar Ishak (Universiti Kebangsaan Malaysia, 2014)
The steady, two-dimensional laminar flow of a power-law fluid over a permeable shrinking sheet of constant surface temperature is investigated. The governing partial differential equations were transformed into a system of nonlinear ordinary differential equations using a similarity transformation, before being solved numerically by the Runge-Kutta-Fehlberg method with shooting technique. The results are presented graphically and the effects of the power-law index n, suction parameter fw and Prandtl number Pr were discussed. It was found that stronger suction is necessary for the solution to exist for a pseudoplastic fluid (n<1) compared to a dilatant fluid (n>1).